Religion and its moral contribution in the school space - Filho, Ademar Henriques da Silva (Seven Editora, 2023)
The main objective of this article is to address the relevance of religion in the promotion of ethical and moral values in school and its influence on the history of education in Brazil, where education and religion were the main sources of formation of citizens. The methodology that supported the research is bibliographic of qualitative nature. We perform readings and files for the production of the article. We approach education from the Jesuit period to the present day. The research concluded the need to still point out new directions that lead religion and education to promote ethical and moral values in school in favor of a just, tolerant and egalitarian society. DOI:https://doi.org/10.56238/ptoketheeducati-014